Seroprevalence of SARS-CoV-2 antibodies in children of United Kingdom healthcare workers: a prospective multicentre cohort study protocol. Issue 11 (19th November 2020) - Corr, Michael; Christie, Sharon; Watson, Chris; Maney, Julieann; Fairley, Derek; Ladhani, Shamez N; Lyttle, Mark David; McFetridge, Lisa; Mitchell, Hannah; Shields, Michael David; McGinn, Claire; McKenna, James; et al.
Abstract : Background: A novel coronavirus SARS-CoV-2 has been responsible for a worldwide pandemic. Children typically have very mild, or no, symptoms of infection. This makes estimations of seroprevalence in children difficult. Research is therefore required to determine the seroprevalence of SARS-CoV-2 antibodies in children. The primary objective of this study is to report the seroprevalence of SARS-CoV-2 IgM and/or IgG antibodies in healthy children at baseline, 2 months and 6 months. This is the only longitudinal UK study of seroprevalence in an exclusively paediatric population. Determining the changing seroprevalence is of vital public health importance and can help inform decisions around the lifting of paediatric specific social distancing measures such as school closures and the cancellation of routine paediatric hospital services. Methods and analysis: 1000 healthy children of healthcare workers aged between 2 and 15 years will be recruited from five UK sites (Belfast, Cardiff, Glasgow, London and Manchester). The children will undergo phlebotomy at baseline, 2 months and 6 months to measure IgM and/or IgG positivity to SARS-CoV-2. A sample size of 675 patients is required to detect a 5% change in seroprevalence at each time point assuming an alpha of 0.05 and a beta of 0.2. Adjusted probabilities for the presence of IgG and/or IgM antibodies and of SARS-CoV-2 infection will be reported using logistic regression models where appropriate. Ethics and dissemination: Ethical approval was obtained from the London - Chelsea Research Ethics Committee (REC Reference—20/HRA/1731) and the Belfast Health & Social Care Trust Research Governance (Reference 19147TW-SW). Results of this study will be made available as preprints and submitted for publication in peer-reviewed journals. Trial registration number: NCT0434740 ; Results